1991
DOI: 10.1136/thx.46.10.732
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of tracheobronchial clearance after sauna in subjects with chronic bronchitis.

Abstract: The effect of sauna on tracheobronchial clearance was studied in five male patients with chronic bronchitis by a radioaerosol technique. No enhancement of tracheobronchial clearance could be detected.Sauna has been shown to cause significant though transient improvement in FEVy in patients with chronic airflow obstruction.' It is also thought to help subjects to acclimatise to rapid temperature changes and to have a bronchodilator effect. The rehabilitation programme for patients with pulmonary diseases in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…During bathing, 12 men with COPD experienced an improvement in FVC and FEV 1 , and most of them described decreased respiratory effort (36). On the other REVIEW hand, bathing did not enhance tracheobronchial clearance in five men with chronic bronchitis (37). Based on this meager evidence on COPD, bathing does not seem to cause any harm, but neither does it improve the condition permanently.…”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…During bathing, 12 men with COPD experienced an improvement in FVC and FEV 1 , and most of them described decreased respiratory effort (36). On the other REVIEW hand, bathing did not enhance tracheobronchial clearance in five men with chronic bronchitis (37). Based on this meager evidence on COPD, bathing does not seem to cause any harm, but neither does it improve the condition permanently.…”
Section: Respiratory Diseasesmentioning
confidence: 99%
“…Various studies have described the influence of sauna bathing on the cardiovascular system [1][2][3][4][5], the autonom ic nervous system [6], the endocrine system [6, 7|, and lung function [8][9][10][11]. With regard to pulmonary per formance.…”
Section: Introductionmentioning
confidence: 99%
“…In Central Europe the sauna has sometimes been recommended as part of the physical treatment of patients with chronic bronchitis. A study 25 on five men (age 50 ± 12 years) with chronic bronchitis showed no enhancement of tracheobronchial clearance, but ill effects of the sauna on the condition of chronic bronchitis have not been published, either.…”
Section: Alleged Risksmentioning
confidence: 95%